A multiparametric study of gold nanoparticles cytotoxicity, internalization and permeability using an in vitro model of blood–brain barrier. Influence of size, shape and capping agent. Issue 7 (9th August 2019) - Enea, Maria; Peixoto de Almeida, Miguel; Eaton, Peter; Dias da Silva, Diana; Pereira, Eulália; Soares, Maria Elisa; Bastos, Maria de Lourdes; Carmo, Helena
Abstract: Gold nanoparticles (AuNPs) have biomedical application on imaging and due to increased optical performance, star-shaped AuNPs are of special interest. Because shape, size and capping greatly influence their toxicokinetics and toxicodynamics, a systematic multiparametric comparative study of the influence of these parameters on the cytotoxicity, internalization, and in vitro permeability was conducted in human Cerebral Microvascular Endothelial Cell line (hCMEC/D3), an in vitro model of the human blood-brain barrier (BBB). AuNPs of different size (14 nm and ∼50 nm), shape (spheres and stars), and coating (11-mercaptoundecanoic acid or MUA and sodium citrate) were synthesized and fully characterized. The time- and concentration-dependent cytotoxic profile of the tested AuNPs differed for the different AuNPs. Generally, toxicity was greater for stars relative to sphere-shaped AuNPs, and citrate coating was more toxic than MUA. Regarding the influence of size, smaller-sized AuNPs were more cytotoxic when compared at the same Au concentration. However, when the concentration of AuNPs was expressed as the number of AuNPs/mL, a higher degree of cytotoxicity was noted for the larger ̴50 nm AuNPs. To understand the influence of size, shape and capping, a systematic study design, in which only one of the variables changes, is determinant for correct data interpretation. Considering the results herein presented, for the sake of comparison of differently-sized AuNPs, it is preferable to design the study based upon the number of nanoparticles, since at a fixed Au concentration the number of particles available to promote effect is higher for smaller-sized AuNPs. Cellular internalization also differed among the tested AuNPs; although all were unable to cross the in vitro BBB, the intracellularly accumulated AuNPs can induce cell damage and later compromise BBB integrity and permeability.